The Status Quo is not viable: Rethinking catholic education in a changed social context - Rymarz, Richard (The Australasian Catholic record, 2024)
To begin this article on a personal note or, as is becoming increasingly in vogue, as an expression of my lived experience, I would like to draw on a very long career in Catholic education. This year (2024), for instance, is the first time in well over twenty-five years that I have not been involved in either teaching students in pre- service programs preparing them to work in Catholic schools or with teachers seeking further accreditation to continue working in Catholic schools. I have written and researched extensively, with much empirical work, on the human community of Catholic education. Alongside all of this I have given countless talks, presentations and seminars on various aspects of Catholic education, most notably in my ‘home base’, religious education. In that time, I have come to realise that what I will call later in this article, the ‘train ’em up’ argument may no longer be sufficient to meet the needs of contemporary Catholic schools.